Legal Tech and the Future of Civil Justice (Cambridge University Press, 2024)
This volume provides judges, lawyers, policymakers, advocates, and anyone interested in the future of the civil justice system with broad and deep guidance on how to seize the opportunities presented by new digital legal technologies. The book also furnishes expert perspectives for avoiding the perils of 'legal tech.'